Semantic Features of German Toponyms. Modern philology: theory, history, methodology - (:unkn) unknown (Rubanets Tetyana, 2024)
Toponymy as an integral part of onomastics deserves serious study in view of its high linguistic, historical and ethnolinguistic content: Place name data help to adjust certain provisions regarding the origins of the language vocabulary in the pre-written period, to identify innovations in the vocabulary of a particular language after its separation from other language families, to clarify their dialectal division, to indicate what processes took place in lexical semantics after the emergence and development of writing.Germanic studies has a large number of scholarly publications devoted to various aspects of the study of the toponymy of German-speaking countries from ancient times to the present. However, as this branch of linguistics develops, new controversial issues arise due to the growing interest in linguistic and extra-linguistic aspects of toponyms, the need to develop methods for comparative and historical studies of place name semantics, and the insufficient study of toponyms in relation to the physical and geographical environment and human mental activity.The purpose of the study is to describe the semantic features of the toponymic system of the German language against a broad typological background. The object of the study is toponyms localized within the modern borders of Germany. The subject of scientific consideration is the semantic, etymological, historical and linguistic-cultural features of German toponyms in different synchronic sections. To achieve this goal, the following tasks are set: (1) to consider the existing approaches to understanding the systemic organization of toponyms; (2) to compile the factual basis for the linguistic description; (3) to describe the semantic features of German place names.To solve specific tasks at different stages of the study, the following methods were used: (1) comparative historical analysis to identify processes taking place at different chronological stages, as well as to identify semantic similarities between place names of different territories; (2) typological analysis to identify common and distinctive semantic characteristics of place 73names denoting different types of geographical objects; (3) etymological analysis to determine the time of origin of a place name, its initial semantic structure and the changes that occur in its semantics over the long period of its existence; (4) statistical analysis to identify quantitative correlations between different semantic groups of place names; (5)semantic analysis to identify extra-linguistic factors that influence the meaning of place names.The research material was based on toponyms from D. Berger’s dictionary “Geographische Namen in Deutschland: Herkunft und Bedeutung der Namen von Ländern, Städten, Bergen und Gewässern”1, published by Duden and considered an academic dictionary. It covers 6,977 names of settlements with more than 1,000 inhabitants, 894 names of rivers and their tributaries with lengths ranging from 10 to 2,000 km, 750 names oflakes with a size of more than 50 hectares, 274 names of mountains with an area of more than 50 m2, and a total of 8,895 place names. The dictionary explains the origins of modern and historical place names for the most famous geographical features of Germany: cities, towns, rivers, lakes, marshes, mountains, caves, forests, nature reserves, physical and geogra-phical territories, historical and ethnographic areas, etc. The etymology of these names reflects the formation of place names in Germany from thetime of the Indo-European ethnolinguistic community and the Great Migration to the present day, as well as centuries of linguistic and extra-linguistic (historical, geographical, ethnographic, cultural) information representing fragments of the linguisticworld picture in the dynamics.To trace the spread of certain place names, we used the German Road Atlas, compiled by ADAC, the German Automobile Club (ADAC)2. The atlas contains the names of all German settlements, updated as of 2023-2024